Estudo comparativo da análise estrutural de um edifício com diferentes alternativas de lançamento da estrutura - Boschi, Gabriel Felipe Peron (2017)
The current state of evolution of the civil construction technologies has as one of its main characteristics a wide variety of viable options in each stage present in this area, with impacts of different scales in the final outcome of a building. The greater range of alternatives available for the execution of each element and activity in a construction results in more decisions to be made by the responsible civil engineer in addition to the decisions related to the structure definition. This paper presents the elaboration of three structural layout proposals for a building case study. The first structure consisted of the adaptation of the case study executed in the building on which the work was based. In the next proposition, the ribbed slab was modified to a solid slab, maintaining the same position of the columns and adding new beams elements. In the last proposition, still using solid slabs, the positions of the pillars and beams were modified. After the three structures were processed through the AltoQi Eberick software, comparisons were made between them in relation to linear static analysis parameters, the resulting strains in their elements and material consumption. Through these comparisons, it was concluded that each alternative presented better results at different points of the analysis, that is, the purpose was not to determine the best proposal, but to analyze in which items each proposal had an advantage. It was also noted, throughout completing the project, the importance of an auxiliary computational software in the calculation of the proposals created, in conjunction with the need for knowledge of one of these tools on the part of the calculating engineers at the present time. The results of this work, therefore, have been demonstrated as satisfactory and relevant, since it was possible to point out significant differences in the results of the different proposals created and the fact that these conclusions could serve as material for study by other professionals interested in the subject.